Rootstock Characteristics of Three Combinations of Theobroma cacao L. Crosses on Different Water Availability - Bayu Setyawan; Niken Puspitasari; Agung Wahyu Susilo; Indah Anita Sari (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Climate change is universal phenomena which is importantly anticipated including cocoa plantation. Drought tolerance cocoa seedling is urgently neededto develop cocoa plantation. This paper studied possible drought tolerance of cocoa seedling through crossing between female parent KKM 22 with three maleparents BAL 209, KW 641, and KW 614. Progeny test was conducted in green house based on four water availability conditions: 25, 50, 75, and 100%. Root condition was recorded as rootstock parameters of three crossings. Result showed that root characteristics varied among crossing samples studied. The longestand hight volume root were recorded from KKM 22 x BAL 209 crossing. Seedling of KKM 22 x BAL 209 crossing tended to have long and wide root, while seedling of KKM 22 x KW 641 crossing tended to have a wide root type and seedling of KKM 22 x KW 614 tended to have a long root type. Based on drought tolerancy, seedling of KKM 22 x KW 641 crossing could be classified as drought tolerance while other two group progenies could be classified as susceptible to drought.To conclude, seedling of KKM 22 x KW 641 can be recommended for cocoa plantation in drought area.